SURVEI PEMBINAAN PRESTASI CABANG OLAHRAGA GULAT SE EKS KARESIDENAN SEMARANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the achievement of sports coaching wrestling Se Ex residency of Semarang.This study used qualitative methods to study Se Ex residency locations covering Semarang, Semarang, Demak, Grobogan, and Kendal. For the samples in this study were administrators, coaches, and athletes. Conclusions from this research is that there is guidance on residency Ex Semarang is sports organizations are structured but not running according to function, coaching running conditions have not been ideal. Advice can be given as follows: 1) It should improve the activities of the organization and implementing appropriate coaching jabatanya function to make it better again. 2) To coach for more firmly to the athletes for athletes keep practicing constantly and discipline. 3) To the athletes to remain diligent practice that ability that has been trained on the increase, in order to perform to the maximum in the face of subsequent competitions. 4) Means and infrastructure to better equipped and updated again. 5) To increase in achievement test match should be done more often.`